The Effectiveness of Google Meet in Online Learning at Students Elementary School - Alifia Indar Cahyani; Maman Suryaman (Jurnal Ilmiah Wahana Pendidikan, 2022)
The development of information technology in the world is so fast, this has resulted in Indonesia especially being affected by this technological development, of course a positive thing for the Indonesian people can also feel the rapid development of technology at this time. Many innovations have sprung up to facilitate all activities that do require technology to streamline and streamline time or production as well as in the field of education. The effectiveness of technology in the field of special education for elementary school children is very influential on their willingness to learn, because there are many impacts that will be caused later on the quality of education or a direct impact on their students because here they use assistive devices such as smartphones which will later cause addiction to gadgets. which is currently difficult to overcome. Therefore, this study was conducted to analyze how effective the use of googlemeet is in online learning methods during a pandemic and what impact online learning will have on elementary school (SD) students. The results of this study are that technological developments are very influential on all fields, especially in the field of education but there are many negative impacts that are caused to children when they are too addicted to the smartphones they use, therefore parental control is very important here to prevent unwanted things